PEDAGOGICAL SIGNIFICANCE OF ACTION GAMES - N.O‘.Hakimova (Scholar Express Journal, 2023)
Pedagogical and educational importance of action games. Some approaches to movement games have been researched, the age difference of students, the content of movement games, the pedagogical value of education with dance and movement houses, speed, dexterity, strength, endurance, flexibility, while physical quality develops comprehensively in movement games
Keywords: speed; dexterity; strength; endurance